Endothelial Mechanosensors for Atheroprone and Atheroprotective Shear Stress Signals - Li H; Zhou WY; Xia YY; Zhang JX (Dove Medical Press, 2022)
Hui Li,* Wen-Ying Zhou,* Yi-Yuan Xia,* Jun-Xia Zhang Department of Cardiology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210006, People's Republic of China*These authors contributed equally to this workCorrespondence: Jun-Xia Zhang, Department of Cardiology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210006, People's Republic of China, Tel +86 15366155682, Email zhangjunshia@njmu.edu.cnAbstract: Vascular endothelial cells (ECs), derived from the mesoderm, form a single layer of squamous cells that covers the inner surface of blood vessels. In addition to being regulated by chemical signals from the extracellular matrix (ECM) and blood, ECs are directly confronted to complex hemodynamic environment. These physical inputs are translated into biochemical signals, dictating multiple aspects of cell behaviour and destination, including growth, differentiation, migration, adhesion, death and survival. Mechanosensors are initial responders to changes in mechanical environments, and the overwhelming majority of them are located on the plasma membrane. Physical forces affect plasma membrane fluidity and change of protein complexes on plasma membrane, accompanied by altering intercellular connections, cell-ECM adhesion, deformation of the cytoskeleton, and consequently, transcriptional responses in shaping specific phenotypes. Among the diverse forces exerted on ECs, shear stress (SS), defined as tangential friction force exerted by blood flow, has been extensively studied, from mechanosensing to mechanotransduction, as well as corresponding phenotypes. However, the precise mechanosensors and signalling pathways that determine atheroprone and atheroprotective phenotypes of arteries remain unclear. Moreover, it is worth to mention that some established mechanosensors of atheroprotective SS, endothelial glycocalyx, for example, might be dismantled by atheroprone SS. Therefore, we provide an overview of the current knowledge on mechanosensors in ECs for SS signals. We emphasize how these ECs coordinate or differentially participate in phenotype regulation induced by atheroprone and atheroprotective SS.Keywords: shear stress, endothelial cells, mechanosensors, mechanotransduction